Analisis Determinan Online Impulse Buying Generasi Milenial Muslim (Gen-M) pada Digital Marketplace di Indonesia - Adita Dyah Asokawati; Achmad Firdaus; Indra (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Rapid revolution in technological developments has brought Indonesia to face changes in economic activities. As the big five internet user in the world Indonesia goverment stimulates the birth of digital marketplace for supporting economic growth, particulary in digital economy. As the result, impulse buying behavior (impulsive purchases) also changed as originally a direct purchase pattern. At the present time, it changes to impulsive buying behavior by online. The aim of this study is to find out how internal factors consist of religiosity and personal factors influence the behavior of Online Impulse Buying and how external factors consist of product marketing factor, stimulus factor, and controlling factor influence the behavior of online impulse buying millennials of muslims on Digital Marketplace in Indonesia. This study consist of three stages,the first, namely literature study on the behavior of Online Impulse Buying. The second, a field study was conducted by distributing questionnaires to 206 respondents. And the last analysis method used is Structural Equation Modeling (SEM) using Partial Least Square (PLS). The result of the study show that personal factor show a significant and positive influence on Online Impulse Buying. The religiosity factor does not have a direct influence on Online Impulse Buying but has influence through personal factors and the results have a significant and positive effect. The controlling factors have a positive effect but do not significantly indicate that the possibility of risk in shopping online. Product marketing factors have a significant but negative influence indicating that the marketing mix has no effect. As for the stimulus factor, it has a significant but negative influence indicating that comments and reviews from other consumers have no effect on the behavior of the Online Impulse Buying Millennials of Muslims. Keywords: Online Impulse Buying, Digital Marketplace, Muslim Millennial Generation (Gen-M).